Pengaruh Kecerdasan Emosional Dan Kecerdasan Spiritual Terhadap Kinerja Karyawan Pada PT. Indomarco Prismatama Makassar - dhiani, nadya putri (LPPM STIEM, 2023)
The performance of employees who have intelligence that is not only intellectual intelligence, but also supported by Emotional Intelligence and Spiritual Intelligence. The effect of emotional intelligence and spiritual intelligence on employee performance is important, because it is one of the markers of employee performance and organizational success and is the key to progress in the present and the future. Relationship with the background of the problem raised in this study is how the employees at PT. Indomarco Prismatama Makassar regarding the influence of emotional intelligence and spiritual intelligence on employee performance. This study aims to examine and analyze the influence of emotional intelligence on employee performance, the influence of spiritual intelligence on employee performance and the influence of dominant variables on employee performance. Data collection uses primary data obtained from employees at PT. Indomarco Prismatama Makassar which was then used as a respondent using the slovin formula after doing the calculations so that the researchers adjusted as many as 82 respondents. The results of the primary data collected through the distribution of the questionnaire have been tested with the classic assumption test in the form of the assumption of normality, the assumption of multicollinearity and the assumption of heteroscedasticity. Methods of data analysis using descriptive statistical analysis techniques and inferential statistical analysis. The results of the study show that emotional intelligence and spiritual intelligence have a positive and significant effect on employee performance and emotional intelligence is the dominant variable that influences employee performance so that all hypotheses proposed are acceptable.